Synthesis of N-succinyl-L,L-diaminopimelic acid mimetics via selective protection - Vaněk, Václav; Pícha, Jan; Buděšínský, Miloš; Šanda, Miloslav; Jiráček, Jiří; Holz, R C; Hlaváček, Jan (Protein peptide letters, 2010)
The search for potential inhibitors that target so far unexplored bacterial enzyme mono-N-succinyl-L,L-diaminopimelic acid desuccinylase (DapE) has stimulated a development of methodology for quick and efficient preparation of mono-N-acylated 2,6-diaminopimelic acid (DAP) derivatives bearing the different carboxyl groups or lipophilic moieties on their amino group.
Keywords: Diaminopimelic Acid; sukcinyldiaminopimeláttransaminasa; vysokoúčinná kapalinová chromatografie; Models, Molecular; acylace; kyselina diaminopimelová; metabolické sítě a dráhy; hmotnostní spektrometrie s elektrosprejovou ionizací; biomimetické materiály; sukcináty; Chromatography, High Pressure Liquid; Metabolic Networks and Pathways; molekulární modely; Acylation; Biomimetic Materials; Succinyldiaminopimelate Transaminase; Spectrometry, Mass, Electrospray Ionization; Succinates